Perbandingan Hasil Koreksi Mata Sipit Menggunakan Scotch Tape Dan Lem Bulu Mata Untuk Rias Pengantin Sumatera Barat - Trisna, Tessa Aida (Jurnal Tata Rias, 2024)
Thin eyes or smaller-looking eyes are a physical feature that is often considered to be unfavourable in some cultures, including in Western Sumatra. Therefore, the eye correction technique is becoming very important in the process of bride embroidery. Some commonly used correction techniques include using scotch tape and eyelash glue. The study aims to compare the use of scotch and eyelash seams against the eyelids in Western Sumatra bride makeup. The study used a quantitative method with two verable groups, namely the scotch tape group and the eyelash sewing group. The research data was collected through the spread of cousions through google forms with makeup artists and brides. The results of this study describe how the use of eyelash glue is more effective for the bride's makeup in the correction of eyebrows. The conclusion of this study is that the use of scotch tape and eyelash glue is a common technique used to correct the eyelids on the bride's makeup. And the results also prove that eyelash glue can create a more impressive look than using scotch tape on Western Sumatra bride makeup.